Biomass production and changes in soil water with cover crop species and mixtures following no-till winter wheat - Kuykendall, Matti Beth (Kansas State University, 2015)
Replacing fallow with cover crops can provide many benefits, including improved soil quality and reduced nitrogen fertilizer requirements. The addition of cover crops into no-till systems has become popular in recent years as a means of increasing cropping system intensity and diversity. A primary concern of producers in the Great Plains is the possibility that cover crops may reduce the amount of soil water stored in the profile for the next grain crop, potentially reducing yields. Multi-species cover crop mixtures that enhance the ecological stability and resilience of cover crop communities may produce greater and more consistent biomass than single species. Field experiments were established in 2013 and 2014 near Belleville and Manhattan, KS following winter wheat (Triticum aestivum L.) harvest to evaluate the effect of cover crop species and species complexity on changes in soil profile water content and water use efficiency. Along with a chemical fallow control, ten cover crop treatments were tested: six single species, two-three component mixes, a mix of six species, and a mix of nine species. Volumetric water content was measured using a neutron probe and a Field Scout TDR 300. Similar data were collected in 2014 from an experiment established in 2007 comparing fallow, double-cropped soybean, and four cover crop types (summer and winter legumes and non-legumes) in a no-till winter wheat-grain sorghum-soybean cropping system near Manhattan, KS. Results from both studies showed that grasses produced the most dry matter with the highest water use efficiency (up to 618 kg cm-1). Fallow lost up to 7.9 cm less water than all cover crop treatments throughout cover crop growth and in the fall, but captured up to 3.4 cm less moisture in the spring than the cover crops that added residue to the soil surface. Brassica species extracted water from deeper in the soil profile than the other cover crop species. Species complexity affected water use only relative to the proportions and productivity of their individual components, with no advantage in water use efficiency for the more complex mixtures.
Keywords: Kansas; Water use; No-till winter wheat; Fallow replacements; Double-crop soybeans; Cover crop mixtures; Agronomy (0285)